Design Thinking Expands Sterilisation of Solar-Powered Medical Devices in Indonesian Private Primary Healthcare - Haudh Al Maa'uun; Esa Iasyabillah Rosyada; Adinda Zahra Raisya Kamil; Arif Rohmansyah Huluq; Amira Khoirunnisa; Siti Zahra Khoirunnisa; Faiz Jihad Al Baihaqi (Renewable Energy Issues, 2025)
Indonesia faces a challenge of conventional energy scarcity in the future. The primary issue with the first-level healthcare industry is its limited use of solar energy, particularly for sterilising medical devices, which is crucial in remote areas to ensure their safety and effectiveness. The research aims to analyse the expansion of solar energy utilisation in the sterilisation of medical devices. The research employs a qualitative method with a grounded theory approach, collecting data through interviews and literature reviews. The research location is at the Rizki Sehat Clinic, Serang Regency, Indonesia. The design thinking approach enables the expansion of solar-powered medical sterilisers in private first-level health facilities, overcoming the limitations of electric and manual sterilisers, which have often been suboptimal due to electricity supply constraints and conventional energy operating costs. This innovation has proven to be efficient and environmentally friendly. It can be implemented gradually through a process that involves identifying needs, designing prototypes, conducting demonstrations, providing training, and expanding to additional facilities. The theoretical implications enrich the literature on the adoption of renewable energy technologies in healthcare. Practically, this study provides systematic implementation guidelines for health facility managers in improving the quality and sustainability of solar-powered medical device sterilisation services. The limitations of research on the scope of a single object, as well as conceptual studies, have not thoroughly evaluated economic aspects across various regions. The subsequent research was conducted in various regions with distinct characteristics, utilising a cost-benefit analysis that incorporated solar power and a digital monitoring system